MEMBANGUN JIWA PEKA (PRODUKTIF, EDUKATIF, KOOPERATIF, DAN AKSI) PADA KARANG TARUNA DI DESA WANI II KECAMATAN TANANTOVEA KABUPATEN DONGGALA - Rizal; Nursalim (Sambulu Gana : Jurnal Pengabdian Masyarakat, 2025)
This community service program aims to develop a sensitive spirit among the younger generation by strengthening the productive, educational, cooperative, and action-oriented aspects of Karang Taruna members in Wani II Village, Tanantovea District, Donggala Regency. The challenges faced include low youth participation in positive activities, underutilization of their potential, and the influence of negative lifestyles that can harm their future. The program's implementation methods included outreach, workshops, skills training, mentoring, and social action activities involving all Karang Taruna members. Results demonstrated increased motivation and social awareness among members, improved organizational management and entrepreneurship skills, and the creation of stronger collaboration among youth. Through this program, Karang Taruna in Wani II Village has transformed into a platform for developing youth character and creativity, while simultaneously serving as a driving force for social development at the village level